2011
DOI: 10.1002/ajmg.b.32010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental contributions to self‐reported thoughts of self‐harm and suicide

Abstract: Thoughts of self-harm and suicidal behavior are thought to be influenced by both genetics and environment. Molecular genetic studies are beginning to address the question of which genes may be involved and whether different genes may be expressed in men and women. We examined thoughts of self-harm and suicidal behavior in a large general population twin sample including male and female same- and opposite-sex twins. In this study, data on self-reported thoughts of self-harm and suicide were obtained from self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…From laboratory studies, we know that people who selfharm display elevated physiological arousal in response to stressors, discontinue or escape stressful tasks sooner, and report greater efforts to suppress aversive thoughts and feelings during their day (Nock 2009). Research on physiological and neurobiological factors, such as pain endurance Kirtley et al 2016) and impulse-control , and on genetic influence (Althoff et al 2012;, is of importance to gain further knowledge of the phenomenon of self-harm at a group level.…”
Section: Self-harm-definition Prevalence Methods and Risk Factorsmentioning
confidence: 99%
“…From laboratory studies, we know that people who selfharm display elevated physiological arousal in response to stressors, discontinue or escape stressful tasks sooner, and report greater efforts to suppress aversive thoughts and feelings during their day (Nock 2009). Research on physiological and neurobiological factors, such as pain endurance Kirtley et al 2016) and impulse-control , and on genetic influence (Althoff et al 2012;, is of importance to gain further knowledge of the phenomenon of self-harm at a group level.…”
Section: Self-harm-definition Prevalence Methods and Risk Factorsmentioning
confidence: 99%
“…Of note, however, the genetic boundaries of these factors were themselves not clean as the factors were moderately intercorrelated and some disorders loaded on more than one factor. Not surprisingly, other studies have shown that symptoms that cut across diagnostic boundaries—psychosis, suicidality, anxiety—are themselves heritable [Cardno et al, ; Eley et al, ; McGuffin et al, ; Althoff et al, ; Trzaskowski et al, ].…”
Section: Genetic Epidemiology and Diagnostic Boundariesmentioning
confidence: 99%
“…Current models of lifetime suicide risk suggest gene-environment interactions, and a recent large twin study supported a liability-threshold model with contributions from additive genetic factors and specific individual environmental influences (Althoff et al, 2012). Suicide and attempted suicide are heritable independent of the associated diagnosis (Currier & Mann, 2008), and adding up to genetic risks, early stress can increase the risk of suicide by influencing the epigenetic regulation of genes involved in stressresponse systems (Turecki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%